Novel pyrrolopyrimidine derivatives: design, synthesis, molecular docking, molecular simulations and biological evaluations as antioxidant and anti-inflammatory agents - Amira I. Sayed; Yara E. Mansour; Mohamed A. Ali; Omnia Aly; Zainab M. Khoder; Ahmed M. Said; Samar S. Fatahala; Rania H. Abd El-Hameed (Taylor & Francis Group, 2022)
Current medical approaches to control the Covid-19 pandemic are either to directly target the SARS-CoV-2 via innovate a defined drug and a safe vaccine or indirectly target the medical complications of the virus. One of the indirect strategies for fighting this virus has been mainly dependent on using anti‐inflammatory drugs to control cytokines storm responsible for severe health complications. We revealed the discovery of novel fused pyrrolopyrimidine derivatives as promising antioxidant and anti-inflammatory agents. The newly synthesised compounds were evaluated for their in vitro anti-inflammatory activity using RAW264.7 cells after stimulation with lipopolysaccharides (LPS). The results revealed that 3a, 4b, and 8e were the most potent analogues. Molecular docking and simulations of these compounds against COX-2, TLR-2 and TLR-4 respectively was performed. The former results were in line with the biological data and proved that 3a, 4b and 8e have potential antioxidant and anti-inflammatory effects.